Job mobility and creative destruction: Flexicurity in the land of Schumpeter - Andreas Kettemann; Francis Kramarz; Josef Zweimüller (University of Zurich, Department of Economics, 2017)
This paper evaluates the 2003 Austrian severance-pay reform, often advocated as a role model for structural reforms in countries plagued by inflexible labor markets and high unemployment. The reform replaced a system with tenure-based severance payments after a layoff (but not after a quit) by payments into pension accounts that accrue to workers after a layoff as well as after a quit. We identify the reform effects using a regression discontinuity (RD) design and find a substantial increase in job mobility in response to the reform. A search-and-matching model with on-the- job search and tenure-dependent severance payments is structurally estimated using the RD-induced empirical moments. Counterfactual policy experiments suggest that flexicurity reforms spur job creation and can substantially reduce unemployment in countries where severance payments are initially high.
Keywords: J63; J65; 330; Severance pay; job mobility; flexicurity